The Role of the University Open to Elderly People (UnAPI/UFMS) in Welcome, Inclusion, Training and Social and Health Education - Righi-Cavallaro, Karina Ocampo; Polisel, Camila Guimaraes; de Carvalho, Leonardo Chaves; Costa, Joao Vitor; Maestri, Maria Eduarda Seno; Dodero, Barbaira Vanzella; Goncalves, Laura Cristine Montanhera; da Silva, Vitoria Ximenes Lopes; Itavo, Camila Celeste Brandao Ferreira; de Souza, Albert Schiaveto (Journal of Sustainability Perspectives, 2025)
Population aging is a direct consequence of the demographic transition underway in Brazil and has generated significant impacts on Brazilian society. During the aging process, individuals  often face situations of vulnerability and social isolation, frequently associated with loneliness, which can compromise their autonomy and independence. In 2018, the Federal University of Mato Grosso do Sul (UFMS) created an institutional university extension program, known as UnAPI - Universidade Aberta à Pessoa Idosa (Open University for the Elderly), designed to welcome and include elderly people within the university environment. The program contributes to the preservation of autonomy and independence, while fostering the development of new social bonds and the exchange of experiences through a wide range of intergenerational activities.This study aims to analyze the program’s development between 2022 and 2025, considering its expansion across different UFMS campuses, the number of vacancies offered, and student enrollment. Currently, UnAPI operates in six cities, carrying out dozens of initiatives every semester. Since its creation, the program has demonstrated consistent growth. Examples of free extension activities offered include: Basic Computing; the Active Life Project, Community Gardening, Oral Health, Choir, Ballroom Dancing, Digital Literacy, Languages and Memory Workshops. UnAPI/UFMS stands out as an innovative and effective strategy for inclusion, training, and social and health education of elderly people in the university context, while also aligning with several Sustainable Development Goals (SDGs), such as SDGs 3, 4, 10, and 11. Moreover, it strengthens opportunities for building friendships and promoting the sharing of knowledge and life experiences.